Playa del Carmen y la dinámica de violencia contra las mujeres en el espacio público turístico - Alma Ivonne Marín Marín; Erika Cruz Coria; Elsa Karen Vázquez Del Valle (Études Caribéennes)
Violence against women (VAW) in the public space is an increasingly visible problem based on feminist reflections and dialogues. However, in tourism studies there is a significant gap regarding this type of analysis. Therefore, it is relevant to identify the experiences of violence of women in the tourist public space, particularly those who reside in cities dedicated exclusively to the sector. For this study, the city of Playa del Carmen (PDC), one of the main destinations in the Mexican Caribbean, was considered as a case of study. Based on a qualitative methodology that focused on testimonial files and in-depth interviews, it was possible to verify that Street Sexual Harassment is a common form of violence in urban experience of women in PDC. In this regard, public transport and dimly lit streets are the spaces in which it occurs recurrently; due to this and other forms of violence manifested in the public space, it is considered a hostile city for the women who inhabit it.